Potential Multifunctional Bioactive Compounds from Dysosma versipellis Explored by Bioaffinity Ultrafiltration-HPLC/MS with Topo I, Topo II, COX-2 and ACE2 - Feng H; Chen G; Zhang Y; Guo M (Dove Medical Press, 2022)
Huixia Feng,1- 4 Guilin Chen,1- 4 Yongli Zhang,1- 4 Mingquan Guo1- 4 1Key Laboratory of Plant Germplasm Enhancement and Specialty Agriculture, Wuhan Botanical Garden, Chinese Academy of Sciences, Wuhan, 430074, People's Republic of China; 2University of Chinese Academy of Sciences, Beijing, 100049, People's Republic of China; 3Sino-Africa Joint Research Center, Chinese Academy of Sciences, Wuhan, 430074, People's Republic of China; 4Innovation Academy for Drug Discovery and Development, Chinese Academy of Sciences, Shanghai, 201203, People's Republic of ChinaCorrespondence: Mingquan Guo, Tel +86-02787700850, Email guomq@wbgcas.cnBackground: Dysosma versipellis (D. versipellis) has been traditionally used as a folk medicine for ages. However, the specific phytochemicals responsible for their correlated anti-inflammatory, anti-proliferative and antiviral activities remain unknown.Purpose: This study aimed to explore the specific active components in D. versipellis responsible for its potential anti-inflammatory, anti-proliferative, and antiviral effects, and further elucidate the corresponding mechanisms of action.Methods: Bioaffinity ultrafiltration coupled to liquid chromatography-mass spectrometry (UF-LC/MS) was firstly hired to fast screen for the anti-inflammatory, anti-proliferative and antiviral compounds from rhizomes of D. versipellis, and then further validation was conducted using in vitro inhibition assays and molecular docking.Results: A total of 12, 12, 9 and 12 phytochemicals with considerable affinities to Topo I, Topo II, COX-2 and ACE2 were fished out, respectively. The anti-proliferative assay in vitro indicated that podophyllotoxin and quercetin exhibited comparably strong inhibitory rates on A549 and HT-29 cells compared with 5-FU and etoposide. Meanwhile, kaempferol displayed prominent dose-dependent inhibition against COX-2 with IC50 value at 0.36 ± 0.02 μM lower than indomethacin at 0.73 ± 0.07 μM. Furthermore, quercetin exerted stronger inhibitory effect against ACE2 with IC50 value at 104.79 ± 8.26 μM comparable to quercetin 3-O-glucoside at 135.25 ± 6.54 μM.Conclusion: We firstly showcased an experimental investigation on the correlations between bioactive phytochemicals of D. versipellis and their multiple drug targets reflecting its potential pharmacological activities, and further constructed a multi-target and multi-component network to decipher its empirical traditional applications. It could not only offer a reliable and valuable experimental basis to better comprehend the curative effects of D. versipellis but also provide more new insights and strategies for other traditional medicinal plants.Graphical Abstract: Keywords: ultrafiltration, Dysosma versipellis, multiple drug targets, anti-inflammatory, anti-proliferative, antiviral